2017
DOI: 10.1590/s1677-5538.ibju.2016.0098
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of short - term functional outcomes and quality of life in a prospective series of brachytherapy and Da Vinci robotic prostatectomy

Abstract: Introduction There is a growing interest in achieving higher survival rates with the lowest morbidity in localized prostate cancer (PC) treatment. Consequently, minimally invasive techniques such as low-dose rate brachytherapy (BT) and robotic-assisted prostatectomy (RALP) have been developed and improved. Comparative analysis of functional outcomes and quality of life in a prospective series of 51BT and 42Da Vinci prostatectomies DVMaterials and Methods Comparative analysis of functional outcomes and quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…In the studies, a total of 61,752 patients underwent primary radical treatment, with 45,002 being treated by RP and 16,750 by BT. Further characterization of the included studies is detailed in Table 1 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). All the studies were published within the last 2 decades.…”
Section: Clinical Characteristics Of Included Studiesmentioning
confidence: 99%
“…In the studies, a total of 61,752 patients underwent primary radical treatment, with 45,002 being treated by RP and 16,750 by BT. Further characterization of the included studies is detailed in Table 1 (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). All the studies were published within the last 2 decades.…”
Section: Clinical Characteristics Of Included Studiesmentioning
confidence: 99%
“…Moreover, patients who underwent LDR‐BT had worsened urinary QOL, as shown in the IPSS and urinary irritative/obstructive domain of EPIC. Previous studies reported worse QOL deterioration in the urinary incontinence domain in patients who underwent prostatectomy 12 and RARP, 3,11 including those who underwent bilateral nerve‐sparing RARP 3 versus LDR‐BT. On the other hand, worse QOL deterioration was noted in the urinary irritative/obstructive domain in patients who received LDR‐BT versus prostatectomy 12 and RARP 3,11 .…”
Section: Discussionmentioning
confidence: 93%
“…Previous studies reported worse QOL deterioration in the urinary incontinence domain in patients who underwent prostatectomy 12 and RARP, 3,11 including those who underwent bilateral nerve‐sparing RARP 3 versus LDR‐BT. On the other hand, worse QOL deterioration was noted in the urinary irritative/obstructive domain in patients who received LDR‐BT versus prostatectomy 12 and RARP 3,11 . Furthermore, in this study, improvement of urinary QOL was also evaluated.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Few studies have been carried out yet to examine the potential benefits of robotic-assisted brachytherapy. Some studies described brachytherapy through surgery with the Da Vinci System in pigs after thoracoscopic wedge resection ( 53 ) and in patients with prostate ( 54 ) or bladder ( 55 ) cancer. There hasn't been any study using brachytherapy with the Da Vinci System in patients with pancreatic adenocarcinoma so far.…”
Section: Applications In Pancreatic Cancer Therapymentioning
confidence: 99%